Penguatan Kapasitas Metode Pembelajaran Bahasa Inggris Pada Madratsah Ibtidaiiyah Negeri 2 Kota Lhokseumawe - Yusnaini; Erlidawati; Arianto, Sofyan; Setiawan; Iba, Zainuddin; Abdurrahman, Al-Chaidar (Universitas Malikussaleh, 2025)
Strengthening the capacity of English language teaching methods at the elementary school level is a strategic step in responding to globalization and improving the quality of education. This research was conducted at MIN 2 Lhokseumawe City, focusing on the development of innovative, interactive, and contextual teaching methods. The approaches used include communicative learning, project-based learning, and the integration of digital media to actively enhance students’ language skills. The initiative involved collaboration among UIN Sultanah Nahrasiah, UNIKI, and Malikussaleh University through teacher training, professional mentoring, and learning evaluation. The results showed increased student interest, engagement, and basic English proficiency. Teachers also became more skilled in designing adaptive and enjoyable learning strategies. This research emphasizes the importance of synergy between madrasahs and universities in developing applicable learning models. It is expected that the outcomes of this initiative will serve as a reference for other madrasahs in improving the effectiveness of English language learning at the elementary level.